A Speckle-Tracking Echocardiography Study: Cardiac Effect of Sleep Duration - Gülsüm Bingöl; Fulya Avcı Demir; Özge Özden; Emre Özmen; Serkan Ünlü (Gazi Medical Journal)
Objective: Sleep is a complex event involving various physiological processes. Recent studies during the last few years have shed light on the effects of sleep duration on health. We investigated the cardiac effects of sleep duration on speckle-tracking echocardiography. We divided the patients into 2 groups who slept more or less than 7 hours and evaluated all of them with transthoracic echocardiography. Methods: This study was a retrospective study was conducted to investigate the cardiac effects of sleep duration. Between June 2021 and February 2022, 129 individuals who were admitted to our hospital for routine check-up with no known chronic disease and with normal and good quality echocardiographic examination were included in the study. The patients who were eligible for the study design were called by the investigator to obtain information on average sleep duration, and two groups were defined by the self-reported sleep duration (≤7 hours, >7 hours per day) and were used in the statistical analyses. Results: A total of 129 patients [≤7 hours (n=80), >7 hours (n=49) per day] were enrolled in this study. All echocardiographic parameters were compared with sleep duration. Among these parameters, left ventricular (LV) global longitudinal strain (GLS) was found to be greater in the group who slept less. (-21.5±2.6 vs. -20.3±2.2 p=0.005). However, being within normal limits, LV end diastolic diameter and right heart chambers were found to be more enlarged in those who slept 7 hours or less than 7 hours. It was also observed that the right atrial volume was higher in the less sleeper group. Conclusion: As a result, GLS, which is one of the parameters showing LV function, was found to be less in healthy people with a sleep time above a certain period, and we believe that this may be a hypothesis to explain the relationship of long sleep time with cardiovascular events.